Cytogenetic analysis and Dlk1-Dio3 locus epigenetic status of mouse embryonic stem cells during early passages - Menzorov, Aleksei (Cytotechnology, 2014)
Mouse embryonic stem (ES) cells are widely used in early development studies and for transgenic animal production; however, a stable karyotype is a prerequisite for their use. We derived 32 ES cell lines of outbred mice (129 × BALB (1B), C57BL × 1B, and DD × 1B F1 hybrids). Pluripotency was assessed by utilizing stem-cell-marker gene expression, teratoma formation assays and the formation of chimeras. It was shown that only 21 of the 32 ES cell lines had a diploid modal number of chromosomes of 40. In these lines, the percentage of diploid cells varied from 30.3 to 78.9 %, and trisomy of chromosomes 1, 8 and 11 was observed in some cells in 16.7, 36.7 and 20.0 % of the diploid ES cell lines, respectively. Some cells had trisomy of chromosomes 6, 9, 12, 14, 18 and 19. In situ hybridization with an X chromosome paint probe revealed that 7 of the 11 XX-cell lines had X chromosome rearrangements in some cells. Analysis of the methylation status of the Dlk1-Dio3 locus showed that imprinting was altered in 4 of the 18 ES cell lines. Thus, mouse ES cell lines are prone to chromosome abnormalities even at early passages. Therefore, routine cytogenetic and imprinting analyses are necessary for ES cell characterization.